ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 71/PUU-XX/2022 TERKAIT PERNIKAHAN BEDA AGAMA - Pidegso, Satrio; Wahyu Prawesthi; Siti Marwiyah (LPPM Universitas Doktor Husni Ingratubun Papua, 2024)
The study aims to analyze the Constitutional Court Decision No. 71/Law-XX/2022, which is an important milestone in Indonesian marriage law, especially in relation to non-religious marriages. Through the study of documents and normative jurisprudential analysis, this study examines the implications of such judgments on the existing social and legal dynamics. The analysis indicates that the Constitutional Court's ruling has given a new and broader interpretation of article 2 of Act No. 1 of 1974 on marriage, which has been the basis for denial of marriage of different religions. The ruling is expected to provide legal clarity and accommodate the religious diversity and beliefs in Indonesia, while reaffirming the importance of protecting human rights in the context of marriage. The study provides recommendations for policymakers to revise and refine existing regulations in order to support the effective implementation of the Constitutional Court rulings.